ON THE CIVIL LIABILITY FOR BREACH OF TITLE INSURANCE CONTRACT - N. V. Petrov (Гуманитарные и юридические исследования)
Within a wide framework of «contract of title insurance», the author examines one of the aspects of legal liability for violation the provisions of the said agreement by the parties. The author challenges the position of a number of national civil law specialists.